Nanoscale mapping of excitonic processes in single-layer MoS2 using tip-enhanced photoluminescence microscopy. Issue 20 (6th May 2016) - Su, Weitao; Kumar, Naresh; Mignuzzi, Sandro; Crain, Jason; Roy, Debdulal
Abstract : Excitonic processes in single-layer MoS2 are mapped for the first time using tip-enhanced photoluminescence and Raman microscopy with 20 nm spatial resolution. Abstract : In two-dimensional (2D) semiconductors, photoluminescence originating from recombination processes involving neutral electron–hole pairs (excitons) and charged complexes (trions) is strongly affected by the localized charge transfer due to inhomogeneous interactions with the local environment and surface defects. Herein, we demonstrate the first nanoscale mapping of excitons and trions in single-layer MoS2 using the full spectral information obtained via tip-enhanced photoluminescence (TEPL) microscopy along with tip-enhanced Raman spectroscopy (TERS) imaging of a 2D flake. Finally, we show the mapping of the PL quenching centre in single-layer MoS2 with an unprecedented spatial resolution of 20 nm. In addition, our research shows that unlike in aperture-scanning near field microscopy, preferential exciton emission mapping at the nanoscale using TEPL and Raman mapping using TERS can be obtained simultaneously using this method that can be used to correlate the structural and excitonic properties.